A 47-Year-Old Stem Cell Transplant Recipient with Fever, Cough and Chest Pain - Omar S Salh; Omar N Nadhem; Sanket R Thakore; Ruba A Halloush; Faisal A Khasawneh (Canadian Respiratory Journal)
Infections and malignancies are among the most serious complications that follow organ or stem cell transplantation. They may have a mild course, and nonspecific and overlapping manifestations. The present article describes a case of symptomatic nodular pulmonary disease that complicated hematopoietic stem cell transplantation. It was diagnosed to be post-transplant lymphoproliferative disorder, a potential sequela of immunosuppression and a very difficult entity to treat in profoundly immunosuppressed patients.